Effect of Partial Shading on the Performance of Various 4×4 PV Array Configurations - Narne, Dharani Kumar; Kumar, T. A. Ramesh; Alla, Rama Koteswara Rao (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
Electrical energy usage has drastically increased in recent decades, resulting in significant demand for renewable energy sources, especially solar. With the development of technology, extracting energy from photovoltaic (PV) modules has become easier and more economical. The performance of PV array decreases under an intermittent environment such as partial shading conditions (PSCs), causing fluctuations in PV array power output. This paper presents the analysis of a 4×4 PV array configuration under different PSCs. The power output of PV array depends on factors such as the type of configuration, size of array, and shading patterns. The performance of various types of 4×4 PV array configurations under different shading situations are compared and analyzed in this study, and the results presented.